Distribution of Ovarian Tumors in Zonguldak Karaelmas University Hospital. Between 2001 and 2007 - Figen Barut; Aykut Barut; Gürkan Kertiş; Sibel Bektaş; Banu Doğan Gün; Burak Bahadır; Gamze Yurdakan; Şükrü Oğuz Özdamar (Medical Network, 2008)
OBJECTIVE: There are numerous types of ovarian tumors, both benign and malignant. The aim of this study was to evaluate the epidemiology of ovarian tumors in Zonguldak and surrounding cities, retrospectively. STUDY DESIGN: Between May 2001 and March 2007, 769 oophorectomy materials from 494 cases which undergo operation for variable cause were reviewed in Department of Pathology. Tumors were classified. RESULTS: Ovarian tumor's ratio was (n: 123) 16.0% in all cases. Distribution of 123 ovarian tumors: 73.2% (90) were benign, 7.3% (9) were borderline tumors and 19.5% (24) were malignant. 68 of the cases (55.3%) were surface epithelial-stromal tumor; 34 of the cases (27.7%) were germ cell tumors; 10 of the cases (8.1%) were sex cord-stromal tumors; one of the cases (0.8%) was vascular tumor and 10 of the cases (8.1%) were metastatic tumors. CONCLUSION: In our study cystadenoma and cystadenocarcinoma were the most frequent benign and malignant tumors respectively and most of them were serous. When compared with the literature, surface epithelial-stromal tumor of the ovary were less frequent, but metastatic tumors to ovary were more frequent in both whole and malignant groups.